Effect of rumen protected thiamine on blood concentration of beta-hydroxyl butyrate in postpartum Holstein cows: a pilot study (Veterinary Science, 2022)
A development of a rumen bypass product containing thiamine might be a valuable alternative on the prevention of ketosis in dairy cattle. The objective of this pilot study was to determine the effects of rumen protected thiamine (RPT) on blood beta-hydroxyl butyrate (BHB) in Holstein postpartum cows. The study was conducted on a dairy herd with 650 cows, randomly assigned to a treatment group (T, n=20) receiving daily for 10 days postpartum, orally, 60 g rumen protected thiamine, and a control group (C, n=20), receiving a placebo. Blood samples were collected on days 3, 7, and 10 after calving. At day 3 and 10 postpartum BHB levels were similar between groups; however, at day 7, BHB concentrations were different (0.57 and 0.83 mmol/L for T and C respectively, P ≤0.05). It is concluded that a rumen protected thiamine oral product decreased the blood concentrations of BHB during the first 10 days postpartum. Based on this pilot study, this additive deserves further investigation to elucidate its potential mechanism of physiological action as a ketosis preventive agent.
Keywords: thiamine; ketosis; beta-hydroxyl butyrate; Holstein; postpartum; cattle